(untitled) (Bangladesh Rice Journal, 2016)
Mechanical intervention in rice (Oryza sativa L.) postharvest operation especially harvesting, threshing and carrying is increasing due to shifting labour from agriculture to non-agricultural sector. It was hypothesized that mechanical intervention in rice postharvest operation will increase the postharvest losses. A two-year study (2008-2010) was conducted during Aus, Aman and Boro seasons in six locations of sadar upazila at Gazipur district to test the hypothesis. The widely used varieties of BR11, BR23, BR26, BR27, BRRI dhan28, BRRI dhan29 were used to assess the losses during harvesting to drying. In the study areas, farmers common practices (harvesting paddy by sickle; transportation by head, shoulder and power tiller operated trolley; threshing by open drum and close drum thresher; cleaning by traditional cleaning device kula and winnower and sun drying) were used to assess the postharvest losses. The average postharvest losses from harvesting to drying recorded 10% in three rice growing seasons. Losses due to mechanical threshing and traditional sun drying were 3.16% and 3.14% respectively. Power tiller operated trolley showed the lowest carrying loss compared to shoulder and head carrying methods. Both kula and winnower were observed as the most appropriate method of grain cleaning. Mechanical intervention in threshing increased the losses, whereas decreased in transportation and winnowing. These data might be used for policy makers to assess the national food grain loss and for researchers to design and development new technology to reduce the postharvest loss. The study should be continued to other regions for consistent results. Bangladesh Rice j. 2016, 20(1): 23-32